Novel dimensionality reduction method, Taelcore, enhances lung transplantation risk prediction - Gouiaa, Fatma; Vomo-Donfack, Kelly L.; Tran-Dinh, Alexy; Morilla, Ian (Elsevier, 2024)
In this work, we present a new approach to predict the risk of acute cellular rejection (ACR) after lung transplantation by using machine learning algorithms, such as Multilayer Perceptron (MLP) or Autoencoder (AE), and combining them with topological data analysis (TDA) tools. Our proposed method, named topological autoencoder with best linear combination for optimal reduction of embeddings (Taelcore), effectively reduces the dimensionality of high-dimensional datasets and yields better results compared to other models. We validate the effectiveness of Taelcore in reducing the prediction error rate on four datasets. Furthermore, we demonstrate that Taelcore’s topological improvements have a positive effect on the majority of the machine learning algorithms used. By providing a new way to diagnose patients and detect complications early, this work contributes to improved clinical outcomes in lung transplantation.
Keywords: Biología molecular; Acute cellular rejection; Topological data analysis; Machine learning; Predictor of ACR risk